# Answer to Question #6505 in Real Analysis for MRK

Question #6505

Let f be a function from A into X, and let Y, Z be proper subsets of X. How do I prove

the inverse function of X = A and

the inverse function of (Y') = the inverse function of (Y)"

the inverse function of X = A and

the inverse function of (Y') = the inverse function of (Y)"

Expert's answer

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment